DESIGN AND BUILD WEB-BASED FREELANCE APPLICATIONS - Kautsar, Daffa Sulthon; Syukriah, Fivi; Desy Kristyawati; Jamilah (International Journal Science and Technology, 2023)
In today's modern era, many people have switched to looking for freelance work. One of the interesting things is freelance work because there is no work attachment to employee status, so that the person can have several jobs at one time. But until now, to find freelance work is not easy because usually many job search applications provide services only for permanent workers. For companies that are looking for freelance labor is also not easy, because freelance job search provider services are also not much. The purpose of designing this Lancer application is to make it easier for people who want to find freelance jobs. This website is designed using UML (Unified MarkUp Language). The method used in building this website uses SDLC (Software Development Life Cycle) which includes the stages of analysis, design, creation, and testing. This website is created using Laravel and MySQL frameworks.